2020
DOI: 10.1177/0192513x20957363
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Social Support and Interracial Divorce in Louisiana

Abstract: This study examines how social support is related to divorce among interracial couples in Louisiana. Using longitudinal, couple-level data from the Marriage Matters Survey, we analyze how measures generally associated with divorce (e.g., couple-level characteristics, individual characteristics, and premarital events) operate similarly within interracial and same-race unions, and whether these measures moderate the relationship between social support and divorce among interracial couples. Results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…External sources of support, such as friends and relatives, were not as effective as support provided by a marital partner ( Bodenmann, 1995 ). Recent study found that external support did not reduce the risk of marital dissolution ( Cammack & Heaton, 2011 ; Grether & Jones, 2020 ; Potter, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…External sources of support, such as friends and relatives, were not as effective as support provided by a marital partner ( Bodenmann, 1995 ). Recent study found that external support did not reduce the risk of marital dissolution ( Cammack & Heaton, 2011 ; Grether & Jones, 2020 ; Potter, 2021 ).…”
Section: Discussionmentioning
confidence: 99%